Rizobacterias promotoras de crecimiento (PGPR) en el biocontrol del nematodo Meloidogyne incognita y Fusarium oxysporum f. sp. lycopersici en el cultivo de tomate (Lycopersicum esculentum). - Muñoz Macías, Byron Israel (2019)
Growth promoting rhizobacteria (PGPR) are named after a group of bacteria that inhabit the rhizosphere of plants and produce benefits such as: enhance their growth, improving the availability or absorption of minerals and other compounds, help the production of hormones needed in the development of vegetables, as well as have the antagonistic capacity against pathogens, therefore, this research has as a general objective to evaluate the PGPR from the germplasm bank of the microbiology laboratory of the State Technical University of Quevedo against the nematode Meloidogyne incognita and the fungus Fusarium oxyporum f. sp. lycopersici in Tomato plants (L. sculentum). In order to evaluate the PGPR responses, two experiments were carried out in vitro and in the greenhouse. The in vitro experiment used the medium Murashige and Skoog (MS), proceeded to inoculate the rhizobacteria 15 days after germination of the plants and after 22 days was inoculated 700 nematodes of M. incognita and 10,000 spores of F. oxyporum f. sp. lycopersici, the number of gills and severity of the disease was evaluated, obtaining greater antagonism with the P. protegens CHAO strain with an average of 1.8 gills per plant and the lesser severity of the disease with 58.75 %. In the greenhouse experiment 2 trials were carried out in which the consortium of five rhizobacteria (P. veroni R4, A. calcoeceticus BMR-12, S. marcescens PM3-8, P. protegens CHA0, E. asburiae PM 3-14) was evaluated against a chemical control (nematicide and fungicide) and a control. For both trials the bacterial consortium was highlighted in the case of M. incognita, the lowest population of J2 nematodes was obtained with an average of 725 nematodes, and a yield of 24,600 Kg/ha. While the trial with F. oxyporum f. sp. lycopersici was evaluated the severity of the disease nine weeks after inoculation obtaining an average of 50% severity and a yield of 19,700 Kg/ha. This proves the effectiveness of PGPR as an alternative in the biocontrol of phytopathogens providing greater protection to crops. Keywords: Rizobacteria, PGPR, antagonist activity.